2020
DOI: 10.3389/fbioe.2020.00679
|View full text |Cite
|
Sign up to set email alerts
|

IGF2BP3 May Contributes to Lung Tumorigenesis by Regulating the Alternative Splicing of PKM

Abstract: RNA binding proteins (RBPs) play a key role in genome regulation. Here we report the post-transcript regulation of IGF2BP3, which belongs to the insulin-like growth factor 2 mRNA binding protein family. We used iRIP-seq and RNA-seq to analyze the transcript regulation and alternative splicing on IGF2BP3 treated with overexpression cells and control. Overexpressed IGF2BP3 has broadly increased genes expression which involved in G-protein coupled receptor signaling pathway, positive regulation of cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 56 publications
4
51
0
Order By: Relevance
“…RBPs are a group of genes that regulate the growth, development and survival of cancer cells, and are closely related to cancer progression ( 30 , 31 ). For instance, IGF2BP3 may contributes to lung tumorigenesis by regulating the alternative splicing of PKM ( 32 ), HuR promotes the progression of head and neck squamous cell carcinoma and bladder cancer ( 33 , 34 ). Therefore, RBPs are potential biomarkers that most likely predict cancer risk and survival outcomes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…RBPs are a group of genes that regulate the growth, development and survival of cancer cells, and are closely related to cancer progression ( 30 , 31 ). For instance, IGF2BP3 may contributes to lung tumorigenesis by regulating the alternative splicing of PKM ( 32 ), HuR promotes the progression of head and neck squamous cell carcinoma and bladder cancer ( 33 , 34 ). Therefore, RBPs are potential biomarkers that most likely predict cancer risk and survival outcomes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Members of the family of insulin-like growth factor 2 mRNA-binding proteins (IMPs, IGF2BPs) are RNA-binding proteins (RBPs) and often summarized in the VICKZ (Vg1 RBP/Vera, IMP-1,2,3, CRD-BP, KOC, ZBP1) group of RBPs (Yisraeli, 2005). A plethora of studies on IMPs describes their functional contexts, including mRNA transport (Eom et al, 2003;Farina et al, 2003;Kwon et al, 2002;Nielsen et al, 2001;Song et al, 2015), mRNA protection (Doyle et al, 1998;Jonson et al, 2014;Muller et al, 2018;Weidensdorfer et al, 2009), progression of various cancers (Doyle et al, 1998;Ioannidis et al, 2003Ioannidis et al, , 2005Liao et al, 2004;Wu et al, 2019), alternative splicing (Xueqing et al, 2020), diabetes and fatty acid metabolism (Regue et al, 2019), and m 6 A-methylation (Huang et al, 2018b). Other overview articles summarize these functions in an integrative (Bell et al, 2013;Degrauwe et al, 2016;Tong et al, 2018) or paralog-focused manner (Christiansen et al, 2009;Dai, 2020;Findeis-Hosey and Xu, 2012;Huang et al, 2018b;Lederer et al, 2014;Mancarella and Scotlandi, 2019;Wang et al, 2021;Xie et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In primary or metastatic cancer, mRNAs IGF2BP3 , HOXA9 , HOXA10 , CEBPG competed with HOXA11-AS mutually, and HOXA10 ( Figure 6B ) as well as IGF2BP3 ( Figure 6C ) were also continuously up-regulated among normal-primary-metastatic process with significant difference in variance analysis. Currently, some studies have demonstrated the association among HOXA10 , IGF2BP3 , and lung cancer ( 29 , 30 ). The results further validated the importance of competitive relationships among HOXA11-AS , IGF2BP3 , and HOXA10 in lung cancer progression.…”
Section: Resultsmentioning
confidence: 99%